If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + (15) = 6 15x + 15 = 6 Reorder the terms: 15 + 15x = 6 Solving 15 + 15x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 15x = 6 + -15 Combine like terms: 15 + -15 = 0 0 + 15x = 6 + -15 15x = 6 + -15 Combine like terms: 6 + -15 = -9 15x = -9 Divide each side by '15'. x = -0.6 Simplifying x = -0.6
| 5(-6n+3)=165 | | -4(-18+6n)=-6(13n+15) | | 3x-7=14+2 | | 4x-4-x=-4 | | 11-3s=8 | | 1(-7x+1)=-55 | | 5(-6+3)=165 | | y=3sinx+-4 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16 | | 7x-3-6x=3 | | (3y-28)/7=y/3 | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.16t | | 15.6t-2(9.3t+15.2)=3.7t+2.9t+4.6t | | 7x+(10)=3 | | (x-28)/7=y/3 | | -5(5x+3)=45 | | 30(c+4)=900 | | 21=x-87+2x | | -19.82+18.5b=-9(-3b-12.72) | | X+0.16X=9600 | | 9(x-3)+3=-15 | | (10+5)*(30+6)=15+36 | | -6x-7x+4=5 | | 21(n+22)=945 | | N-1-3=-1 | | 2m+4n=12 | | 7(7r+19)=7-14r | | 12x+3=-10 | | -8x+4x+6x=-6 | | -12x+2y=-14 | | 3(7h-15)=9+18h | | -7(7-3x)=-175 |